Qualitative investigations of boundary value problem for self‐similar second order system which arises from modeling of surface chemical reactions - Jānis Cepitis (Mathematical Modelling and Analysis, 1997)
„Qualitative investigations of boundary value problem for self‐similar second order system which arises from modeling of surface chemical reactions" Mathematical Modelling Analysis, 2(1), p. 41-47